An in vitro potency assay using nicotinic acetylcholine receptor binding works well with antivenoms against Bungarus candidus and Naja naja - Ratanabanangkoon, K.; Simsiriwong, P.; Pruksaphon, K.; Tan, K.Y.; Chantrathonkul, B.; Eursakun, S.; Tan, C.H. (Nature Publishing Group, 2018)
In order to facilitate/expedite the production of effective and affordable snake antivenoms, a novel in vitro potency assay was previously developed. The assay is based on an antiserum's ability to bind to postsynaptic neurotoxin (PSNT) and thereby inhibit the PSNT binding to the nicotinic acetylcholine receptor (nAChR). The assay was shown to work well with antiserum against Thai Naja kaouthia which produces predominantly the lethal PSNTs. In this work, the assay is demonstrated to work well with antiserum/antivenom against Bungarus candidus (BC), which also produces lethal presynaptic neurotoxins, as well as antivenom against Sri Lankan Naja naja (NN), which produces an abundance of cytotoxins. The in vitro and in vivo median effective ratios (ER50s) for various batches of antisera against BC showed a correlation (R 2) of 0.8922 (p < 0.001) while the corresponding value for the anti-NN antivenom was R 2 = 0.7898 (p < 0.01). These results, together with the known toxin profiles of various genera of elapids, suggest that this in vitro assay could be used with antisera against other species of Bungarus and Naja and possibly other neurotoxic snake venoms worldwide. The assay should significantly save numerous lives of mice and accelerate production of life-saving antivenoms.